1991
DOI: 10.1084/jem.173.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Interferon gamma and tumor necrosis factor have a role in tumor regressions mediated by murine CD8+ tumor-infiltrating lymphocytes.

Abstract: SummaryWe have investigated the mechanisms whereby adoptively transferred murine CD8+ lymphocytes mediate tumor regressions. Noncytolytic, CD8+ tumor-infiltrating lymphocytes (TIL) eradicated established lung tumors in irradiated mice. Many cytolytic and noncytolytic CD8+ TIL cultures specifically secreted interferon y (IFN-y) and tumor necrosis factor when stimulated with tumor cells in vitro. The effectiveness ofTIL when adoptively transferred to micebearing micrometastases correlated better with their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
161
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(173 citation statements)
references
References 36 publications
11
161
0
1
Order By: Relevance
“…This model allowed us to show that Renca lung metastases could be destroyed efficiently in the complete absence of perforin and granule-mediated cytotoxicity. These findings extend previous reports on clearance of lung metastases by CTL in a variety of murine tumors (33), as well as the murine melanoma model B16BL6-D5 (34), and the murine sarcomas MCA-310 (34) and . In the aforementioned studies, tumor-draining lymph node (TDLN) cells that had been expanded in vitro with anti-CD3 and IL-2 were used as a source of effector T cells.…”
Section: Discussionsupporting
confidence: 89%
“…This model allowed us to show that Renca lung metastases could be destroyed efficiently in the complete absence of perforin and granule-mediated cytotoxicity. These findings extend previous reports on clearance of lung metastases by CTL in a variety of murine tumors (33), as well as the murine melanoma model B16BL6-D5 (34), and the murine sarcomas MCA-310 (34) and . In the aforementioned studies, tumor-draining lymph node (TDLN) cells that had been expanded in vitro with anti-CD3 and IL-2 were used as a source of effector T cells.…”
Section: Discussionsupporting
confidence: 89%
“…The central role of CD8 T cells in anti-tumor immunity has been established from data compiled in both animal model systems and human clinical trials [21][22][23][24][25]. As the primary effector cells of the cellular immune system, CD8 T cells are involved in the direct recognition and eradication of tumor cells through both cytokine production and cytolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The release of soluble factors represents an additional mechanism by which CD8 T cells could exert anti-tumor activity. An early study in mice revealed that rejection of pulmonary metastases by cultured tumorspecific CD8 T cells correlates better with their capacity to produce IFN-c than with their cytotoxicity in vitro [18]. More recent studies using IFN-c-deficient mice have provided compelling evidence for the important role of IFN-c in T cell-mediated tumor cell rejection [7,9,10,13,14,[19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%